Population displacement due to river erosion in Sirajganj district: Impact on food security and socio-economic status - Shetu, MSR; Islam, MA; Rahman, KMM; Anisuzzaman, M (Journal of the Bangladesh Agricultural University, 2017)
As a consequence of river bank erosion, every year a huge number of people displace from their native houses to some other areas in Sirajganj district. This study was conducted to measure the economic losses and also assess the status of food security of the displaced people of Sirajganj by using primary data collected from respondents of four Upazilla (sub-district) of Sirajganj, namely, Shahjadpur, Kazipur, Belkuchi, and Sirajganj Sadar. In evaluating the food security, direct calorie intake (DCI) and protein intake method had been applied. The study has shown that 58.3% and 15% of the total respondents are found to be food secure on the basis of calorie and protein intake respectively. In addition of assessing food security, the single-level binary logistic regression model and also multinomial logistic regression were fitted to find out the important determinants of food security of the displaced people living in Sirajganj and also in the other regions of Bangladesh where people shift their houses to other places because of river erosion. The level of income was found as positively significant, however, the age of the family head and the family size were found as negatively significant determinant of the food security both on the basis of calorie and protein intake. The other significant determinants that had been identified are- duration after shifting, losses due to shifting, and education of the family head. The study has recommended some actions to the government, concerned stakeholders, GOs or NGOs and others to ensure the food security of the displaced people. They are- preventing river erosion, increasing level of education, controlling of the population, initiating improved agricultural farming, ensuring vocational training for the affected people, encouraging women empowerment et cetera. J. Bangladesh Agril. Univ. 14(2): 191-199, December 2016